1992
DOI: 10.1007/bf02751105
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial terpenes from oleoresin of ponderosa pine treePinus ponderosa: A defense mechanism against microbial invasion

Abstract: The oleoresin of the ponderosa pine,Pinus ponderosa (Pinaceae) exhibited broad antimicrobial activity. In order to identify the active compounds, the oleoresin was steam distilled to give a distillate and residue. The distillate contained mainly monoterpenes and some sesquiterpenes, while the residue consisted chiefly of four structurally related diterpene acids. An antimicrobial assay with the pure compounds indicated that the monoterpenes were active primarily against fungi, but there was also some activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 21 publications
3
77
1
Order By: Relevance
“…During our experiment, the fungal inoculated lodgepole pine seedlings always released more α-pinene than the controls. Resin monoterpenes from ponderosa pine including α-and β-pinene, 3-carene, limonene, and terpinolene have antifungal properties (Himejima et al, 1992). Monoterpenes and other chemical compounds in the resin of host pine inhibit the growth of bark beetle-associated fungi in the southern US coniferous system (Bridges, 1987;Klepzig et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…During our experiment, the fungal inoculated lodgepole pine seedlings always released more α-pinene than the controls. Resin monoterpenes from ponderosa pine including α-and β-pinene, 3-carene, limonene, and terpinolene have antifungal properties (Himejima et al, 1992). Monoterpenes and other chemical compounds in the resin of host pine inhibit the growth of bark beetle-associated fungi in the southern US coniferous system (Bridges, 1987;Klepzig et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that sesquiterpenes (m/z=205) also produce fragments at m/z 137 and 81, with ratios of the fragment to m/z 205 count rate varying significantly between β-caryophyllene and α-humulene, from 0.11 (cps 137/cps 205) and 0.26 (cps 81/cps 205) for α-humulene, and 0.30 and 0.62 for β-caryophyllene. The sesquiterpenes, α-longipinene, longifolene, and germacrene D have been identified in the oleoresin distillates of ponderosa pine (Himejima et al, 1992), however the sesquiterpene signal at m/z 205, monitored in Summer 2003, never exceeded 5% of the signal at m/z 81 and 137. Therefore, fragmentation of sesquiterpenes onto the monoterpene masses should only be a minor issue.…”
Section: Methodsmentioning
confidence: 99%
“…Diterpene acids (e.g., abietic, levopimaric, neoabietic, and palustric acids) have been isolated from ponderosa pine oleoresin (Anderson et al, 1969;Himejima et al, 1992) and these are known from other conifers to be antifeedants against aphids and sawflies (Wagner et al, 1983;Schuh and Benjamin, 1984;Rose et al, 1981). but have not been tested on bark beetles.…”
Section: Feeding Stimulants and Deterrentsmentioning
confidence: 99%
“…A phenylpropanoid, 4-allylanisole, from P. taeda resin inhibited growth of all fungi tested. Himejima et al (1992) steam-distilled ponderosa pine oleoresin into a distillate of monoterpenes and sesquiterpenes and a residue of four diterpene acids. The individual monoterpenes of the distillate were not inhibitory to growth of several gram-positive bacteria (at 800 pgtml) but did inhibit two species of fungi.…”
Section: Plant Compounds and Resin In Resistance Mechanismsmentioning
confidence: 99%